Athletes health during pandemic times: Hospitalization rates and variables related to COVID-19 prevalence among endurance athletes - Braga da Silva, F.; Fonseca, B.; Domecg, F.; Riccio Facio, M.; Prado, C.; Toledo, L.; Tuche, W. (International Journal of Cardiovascular Sciences, 2021)
Background: The SARS-COV2 pandemic has deeply affected the availability for training and competing for recreational and professional athletes. However, to date, the disease`s course among the athletic population has not been *studied .